Triterpenoid modulation of IL-17 and Nrf-2 expression ameliorates neuroinflammation and promotes remyelination in autoimmune encephalomyelitis - Pareek, Tej K. (Nature Publishing Group, 2011)
Inflammatory cytokines and endogenous anti-oxidants are variables affecting disease progression in multiple sclerosis (MS). Here we demonstrate the dual capacity of triterpenoids to simultaneously repress production of IL-17 and other pro-inflammatory mediators while exerting neuroprotective effects directly through Nrf2-dependent induction of anti-oxidant genes. Derivatives of the natural triterpene oleanolic acid, namely CDDO-trifluoroethyl-amide (CDDO-TFEA), completely suppressed disease in a murine model of MS, experimental autoimmune encephalomyelitis (EAE), by inhibiting Th1 and Th17 mRNA and cytokine production. Encephalitogenic T cells recovered from treated mice were hypo-responsive to myelin antigen and failed to adoptively transfer the disease. Microarray analyses showed significant suppression of pro-inflammatory transcripts with concomitant induction of anti-inflammatory genes including Ptgds and Hsd11b1. Finally, triterpenoids induced oligodendrocyte maturation in vitro and enhanced myelin repair in an LPC-induced non-inflammatory model of demyelination in vivo. These results demonstrate the unique potential of triterpenoid derivatives for the treatment of neuroinflammatory disorders such as MS.